Relationship between resilience and mobbing in basic education teachers of the Achocalla Municipality - Olivares Alvares, David Max (2024)
Mobbing and resilience are antagonistic factors of great impact on the economy of organizations that affect the physical-psychological health of the individual. For this reason, the objective of the study was to determine the type of relationship betweenthem, taking as a reference basic education teachers in the Municipality of Achocalla, Bolivia. The methodology had a quantitative approach, with a descriptive level and a non-experimental design. Among the results, 57% of the teachers have suffered mobbing, while 43% of the female teachers have suffered mobbing; likewise, 74.8% of the teaching staff have experienced psychological violence and although 50.4% of the teachers show an average strength to overcome it, only 23% show a high level of resilience. It was concluded that there are inverse relationships between: “Resilience and Mobbing”; “Self- view and Mobbing”; “View of the problem and Mobbing”; “Resilient response and Mobbing”.